2020
DOI: 10.3390/foods9101466
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Attributes and Sensory Quality during Storage Time of Spiced Lamb Burgers from Manchego Spanish Breed

Abstract: The aim of this study was to determine the effect of the addition of spices (garlic, rosemary, thyme, sage or clove) on the chemical and sensory characteristics of burgers elaborated with lamb meat from different locations (L: only leg; LNB 2/3 leg + 1/3 neck and breast). Formulation type (L vs. LNB) modified the chemical composition. L burgers showed lower values of fat, saturated fatty acids, monounsaturated fatty acids and higher moisture and polyunsaturated fatty acids content than LNB samples, with both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Protein content in all cases varied between 16.63 and 17.63 g/100 g of product, with no differences (p ≥ 0.05) among batches. These values are slightly lower than the values typically found in lamb meat [37,38]. Reyes-Padilla et al [36] and Jiménez Colmenero et al [39] obtained similar results on protein content (p < 0.05) due to the addition of walnuts in low-fat bologna-type meat and restructured beef steaks, respectively, since they did not find variations in protein content, although the reported protein values are slightly higher than ours.…”
Section: Effects Of the Various Portions Of Added Pecan Nuts On Nutri...supporting
confidence: 80%
“…Protein content in all cases varied between 16.63 and 17.63 g/100 g of product, with no differences (p ≥ 0.05) among batches. These values are slightly lower than the values typically found in lamb meat [37,38]. Reyes-Padilla et al [36] and Jiménez Colmenero et al [39] obtained similar results on protein content (p < 0.05) due to the addition of walnuts in low-fat bologna-type meat and restructured beef steaks, respectively, since they did not find variations in protein content, although the reported protein values are slightly higher than ours.…”
Section: Effects Of the Various Portions Of Added Pecan Nuts On Nutri...supporting
confidence: 80%
“…Shahidi (2016) described the factors that influence lipid oxidation of meat products and among them, the content of unsaturated fatty acids is considered a relevant element. Precisely, our previous study (Linares et al, 2020) showed the richness of lamb burgers in these constituents. Lipid oxidation involves the formation of toxic compounds such as peroxides, aldehydes and ketones, which decrease the shelf life of food and turn products unsatisfactory for consumers (Özcan & Arslan., 2011).…”
Section: Lipid Oxidationmentioning
confidence: 78%
“…Garlic addition to raw pork minced meat significantly increased the content of linoleic acid and protected fatty acids from oxidation [ 31 ]. However, when adding thyme, rosemary, clove, and garlic to lamb burgers, no significant differences were reported in fatty acid profiles between treated samples [ 32 ].…”
Section: Discussionmentioning
confidence: 99%